Facial tremor in patients with Parkinson’s disease: prevalence, determinants and impacts on disease progression - Ou, Ruwei (BMC Neurol, 2021)
BACKGROUND: Facial (lip and jaw) tremor (FT) is associated with Parkinson’s disease (PD) but few studies have been conducted to explore its clinical profile. We performed this study to investigate the prevalence and clinical correlates of FT in PD, and further to evaluate its effect on disease progression. METHODS: A retrospective, cross-sectional (n = 2224) and longitudinal (n = 674) study was conducted. The presence of FT was based on a ≥ 1 score in the United PD Rating Scale (UPDRS) item 20A. Group comparisons were conducted, followed by a forward binary logistic regression analysis. Inverse probability of treatment weighting (IPTW) based on the propensity score and weighted or unweighted Cox regression models were used to explore the impact of FT on five clinical milestones including death, UPDRS III 11-point increase, Hoehn and Yahr (H&Y) stage reaching 3, dyskinesia development, and Montreal Cognitive Assessment 3-point decrease. RESULTS: FT was presented in 403 patients (18.1%), which showed increasing trends with disease duration and H&Y score. Age (P < 0.001), female (P < 0.001), disease duration (P = 0.001), speech (P = 0.011), rigidity (P = 0.026), rest tremor on limbs (P < 0.001), kinetic tremor on hands (P < 0.001), and axial symptoms (P = 0.013) were independent factors associated with FT. Both unweighted and weighted Cox regression models indicated that baseline FT and FT as the initial symptom were not associated with the five outcomes. CONCLUSIONS: Our study suggested that FT was not uncommon and provided a deeper insight into the characteristics of FT in PD. The predict value of FT on long-term progronis of PD may need future longer follwe-up study. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12883-021-02105-y.